(untitled) (Global Journal of Human-Social Science, 2017)
The right to access to justice is one of core human rights that is fundamental to ensure full protection of human rights. The right is recognized in almost all international and regional human rights treaties; including those Ethiopia is member. The Federal Democratic Republic of Ethiopia Constitution also clearly recognized the right. Among others, the right imposes upon States the obligation to set up all appropriate legal and institutional frameworks that address claims of violations of rights. Specifically, States have the obligation to adopt appropriate legislations; put in place competent judicial and quasi-judicial organs; ensure accessibility and effective functioning of those organs; and guarantee fair trial rights in proceedings. As a State party to different international and regional human rights treaties, and to fulfill the Constitutional pledge, Ethiopia has the obligation to ensure that the right to access to justice is fully protected and fulfilled throughout the nation.